Effect of cultivars and fertilizer levels on growth, yield and quality of patchouli [Pogostemon cablin (Blanco) Benth.] under shaded condition - Neha Guleria, Munnu Singh, (Journal of Spices and Aromatic Crops, 2012)
A field experiment was conducted at Bengaluru (Karnataka) to study the influence of culivars (Johore and CIM-shreshtha) and three fertilizer levels [Control (no fertilizers); recommended NPK (200:50:50 kg ha-1) and vermicompost 10 t ha-1 + 50% recommended NPK (100:25:25 kg ha-1)] on growth, herbage and oil yield of patchouli under shaded condition. Results showed that among the cultivars, CIM-shreshtha recorded significantly higher plant height and plant spread than Johore. CIM-shreshtha produced 29.25% and 43.28% higher herbage and oil yield compared to Johore. The application of recommended NPK (200:50:50 kg ha-1) produced maximum herbage and oil yield compared with control and was at par with vermicompost 10 t ha-1 + 50% recommended NPK (100:25:25 kg ha-1). Oil quality was not influenced by cultivar and fertilizer levels.